Responsibility and Climate Change: A Comparative Ethical Analysis of World Religions - Mawardi, Mawardi; Anzaikhan, M.; Tanggok, M. Ikhsan (Religió Jurnal Studi Agama-agama, 2026)
This article develops a comparative normative convergence model as a foundation for climate justice. Through critical examination of normative corpora across Islam, Christianity, Hinduism, Buddhism, and Confucianism, the study demonstrates that each tradition contains principles of trusteeship, interdependence, moderation, and justice that can be formulated as shared public ethical categories without erasing distinct theological commitments. This synthesis is achieved through dialectical engagement with internal tensions: between anthropocentrism and ecological responsibility, between personal ethics and structural justice, and between normative ideal and institutional practice. Islam emphasizes amānah (trusteeship) and moderation; Christianity advances stewardship and climate justice; Hinduism and Buddhism highlight cosmic interdependence and the transformation of consciousness; Confucian thought grounds ecological responsibility in relational self-cultivation and principled moderation (Zhongyong). The findings indicate that religion’s contribution to climate governance depends less on doctrinal convergence at the theological level than on its capacity to translate particular values into structurally engaged, postcolonially aware, and politically courageous public action. The study concludes that the comparative normative convergence model advances the field by demonstrating that synthesis is not found but constructed.